Experience in the Presentation of ABET Criterion 5 on Curriculum in the Accreditation Process of an Engineering Professional School (LACCEI, 2024)
The present work shows the experience in the presentation of Criterion 5 of ABET on the Curriculum of an Engineering Professional School of the Universidad Nacional de San Agustín de Arequipa - Peru. It includes two aspects, the presentation of Criterion 5 in the Self-study Report and the presentation of the evidence before the ABET evaluation team. The recommendations to follow to avoid deficiencies, weaknesses, concerns and observations for this criterion in an accreditation process are highlighted, the key points to achieve accreditation are also detailed, and the results obtained by applying the recommendations proposed for this criterion within an accreditation process with ABET